If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 13 = 34 + -12x Reorder the terms: 13 + 10x = 34 + -12x Solving 13 + 10x = 34 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 13 + 10x + 12x = 34 + -12x + 12x Combine like terms: 10x + 12x = 22x 13 + 22x = 34 + -12x + 12x Combine like terms: -12x + 12x = 0 13 + 22x = 34 + 0 13 + 22x = 34 Add '-13' to each side of the equation. 13 + -13 + 22x = 34 + -13 Combine like terms: 13 + -13 = 0 0 + 22x = 34 + -13 22x = 34 + -13 Combine like terms: 34 + -13 = 21 22x = 21 Divide each side by '22'. x = 0.9545454545 Simplifying x = 0.9545454545
| 9f=7f-14 | | 33x-8=7 | | Y=21x+7 | | 4x/3=3x-5/2 | | 2x+20=25-9x | | 25x+10=58 | | 2x-7-4x+3=2x-4x-7 | | 6z^2+3=729 | | 123/3 | | 15-t+8y=-13 | | 4/13/6.5 | | x^2(x-13)-2(2x-7)= | | (4x+1)+(11+2x)=90 | | 6=48/x | | -19-2c=-c | | 64w-56w=56w | | (4x+1)+(11+2)=90 | | 2-14/-4 | | X/12=7/8 | | 35x+y+15=180 | | 2u+11=37 | | -3x/2=7/8 | | 9x+7b=267000 | | v^2=52 | | ((x^2)-(2x))-9=0 | | 28=5w-12 | | C=5+ab | | 292-200/4=x | | 7x-6x+8x=24 | | 3r^2-2=52.18 | | 4x+2(24-x)=60 | | 5u+17=72 |